Enhanced immunogenic potential of cancer immunotherapy antibodies in human IgG1 transgenic mice. Issue 1 (31st December 2022) - Egli, Jerome; Heiler, Stefan; Weber, Felix; Steiner, Guido; Schwandt, Timo; Bray-French, Katharine; Klein, Christian; Fenn, Sebastian; Lotz, Gregor P.; Opolka-Hoffmann, Eugenia; Kraft, Thomas E.; Petersen, Laetitia; et al.
ABSTRACT: Clinical anti-drug-antibody (ADA) responses represent a substantial obstacle to the development of efficacious therapeutic antibodies. The enhanced ADA production against the idiotype (Id) often displayed by cancer immunotherapy antibodies (CitAbs) can lead to exposure loss and subsequently affect anti-tumor efficacy and cause undesired effects on safety. Thus, ADA responses contribute to prolonged clinical development and high attrition rates. Most conventional therapeutic antibodies are now of human origin or humanized proteins, and are hence immunologically tolerized in most patients. In contrast, the contribution of additional factors, other than the protein sequence, to the higher rates of clinical ADA to certain CitAbs, remains poorly understood. Here, we used human immunoglobulin gamma 1 (IgG1) transgenic mice (named "hIgG1 transgenic mice" or "TG"), which are immunologically tolerant to human IgG1, to study the immunogenicity of 13 conventional antibodies and 2 CitAbs. We found that tolerance to non-germline encoded Ids is maintained in part by the function of neonatal Fc-receptor (FcRn). Additionally, the incorporation of T cell-engaging moieties like an interleukin 2 (IL-2)-based immunocytokine or a CD3ε-specific antigen-binding fragment (Fab) was sufficient to revert tolerance and trigger ADA production directed to the Id of these compounds. We postulate that T cell receptor or IL-2 receptor activation may result in activation of unresponsive T cells specific for the crystallizable fragment (Fc) that typically inactivate Id-specific B cells and mediate "linked-antigen tolerance". Reversal of this unresponsiveness by the action of CitAbs on T cells may be the cause of undesired ADA responses. Abbreviations: ADA Anti-Drug Antibodies; BCR B Cell Receptor; BId Idiotype-specific B Cell; BiTE Bispecific T cell Engager; BMC Bone Marrow Chimeric Mice; BSA Bovine Serum Albumin; CDR Complementary Determining Region; CEA Carcinoembryonic Antigen; CIT Cancer Immunotherapy; CitAbs Cancer Immunotherapy Antibodies; DC Dendritic Cell; ELISA Enzyme-Linked Immunosorbent Assay; FcRn Neonatal Fc Receptor; FcyR Fc gamma Receptor; GM-CSF Granulocyte-Macrophage Colony Stimulating Factor; gMFI Geometric Mean Fluorescence Intensity; H Heavy Chain; IC Immune Complex; Id Idiotype; IgA Immunoglobulin alpha; IgG1 Immunoglobulin gamma 1; IL-2 Interleukin 2; IL-2R Interleukin 2 Receptor; IL2v Interleukin 2 Variant; IVIG1 Intravenous Immunoglobulin 1; KLH Keyhole Limpet Hemocyanin; L Light Chain; MAPPs MHC-associated Peptide Proteomics; MHC Major Histocompatibility Complex; PBMC Peripheral Blood Mononuclear Cells; PBS Phosphate Buffered Saline; SHM Somatic Hypermutation; scFv Single-chain Variable Fragment; TCR T cell Receptor; TFc Fc-specific T cell; TId Id-specific T cell; UV Ultraviolet; V Variable.